HEALTH AS HARMONY: EVOLUTION OF THE HEALTHY LIFESTYLE IDEA FROM ANTIQUITY TO GLOBAL MODERNITY - Gadoyeva Lobar Ergashevna (Western European Studies, 2026)
The article “Health as Harmony: Evolution of the Healthy Lifestyle Idea from Antiquity to Global Modernity” examines the historical and philosophical transformation of the concept of health as a harmonious state of body, mind, and social existence. The study traces the origins of the harmony paradigm in ancient Greek thought, particularly in the ethical and medical traditions associated with Hippocrates and Aristotle, where health was understood as balance (eucrasia) and moderation (mesotes).The research further analyzes medieval and early modern reinterpretations of health within religious and humanistic frameworks, emphasizing the moral dimension of bodily discipline and spiritual integrity. In modernity, the biomedical model redefined health primarily as the absence of disease; however, the 20th century witnessed a paradigmatic shift toward a holistic understanding, reflected in the definition proposed by the World Health Organization, which conceptualizes health as complete physical, mental, and social well-being.
Keywords: health; harmony; healthy lifestyle; antiquity